2008
DOI: 10.1007/s00285-008-0211-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale agent-based cancer modeling

Abstract: Agent-based modeling (ABM) is an in silico technique that is being used in a variety of research areas such as in social sciences, economics and increasingly in biomedicine as an interdisciplinary tool to study the dynamics of complex systems. Here, we describe its applicability to integrative tumor biology research by introducing a multi-scale tumor modeling platform that understands brain cancer as a complex dynamic biosystem. We summarize significant findings of this work, and discuss both challenges and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
117
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 49 publications
0
117
0
Order By: Relevance
“…Chen et al [121] study cancer cell motility focusing the ways to optimize the spatial search strategies, Zhang et al [127,128] propose a multi-scale tumor modeling platform that understands brain cancer, As concerning the basic structure and ingredients of a standard agent-based model built into the field of biology and medicine [110,111,125,129,130], the diverse types of agents, their behaviors (mechanisms of interaction), and their environment should be distinguished [103,131]. All these aspects are discussed in the next section with reference to our model that, placing at a quite abstract level of simulation, models the interactions of a population of tumor cells with a population of peptides and other regulatory molecules, like micro-RNA.…”
Section: Review Of Agent Based Simulation In Can-cer Researchmentioning
confidence: 99%
“…Chen et al [121] study cancer cell motility focusing the ways to optimize the spatial search strategies, Zhang et al [127,128] propose a multi-scale tumor modeling platform that understands brain cancer, As concerning the basic structure and ingredients of a standard agent-based model built into the field of biology and medicine [110,111,125,129,130], the diverse types of agents, their behaviors (mechanisms of interaction), and their environment should be distinguished [103,131]. All these aspects are discussed in the next section with reference to our model that, placing at a quite abstract level of simulation, models the interactions of a population of tumor cells with a population of peptides and other regulatory molecules, like micro-RNA.…”
Section: Review Of Agent Based Simulation In Can-cer Researchmentioning
confidence: 99%
“…In these methods, interactions between autonomous individuals are simulated. They have been successfully employed to simulate, for instance, bacterial chemo-taxis (Shimizu et al 2003), tissue formation and developmental processes (reviewed in Thorne et al 2007) and cancer growth (Wang et al 2007;Zhang et al 2009). A related approach is the use of rule-based models, where actual reactions are not described, but only the rules to generate them during simulations (e.g.…”
Section: Entering Mathematical Relations and Numerical Valuesmentioning
confidence: 99%
“…ABM rely on the interactions between agents and with the environment. ABM are usually the best choice to model and simulate complex systems that cannot be globally simulated but where local rules are well known [43].…”
Section: Cell Description With Cellular Automata or Agent-based Modelsmentioning
confidence: 99%
“…Many special issues in journals [27,34] or reviews have been written on the topic of hybrid modelling in biology, either explicitly or implicitly by focusing on related topics such as multiscale modelling [3,28,43], complexity in biology [9], systems and integrative biology [19,22,23]. Reviews dedicated to some specific applications of hybrid models can also be found, for example in biological networks modelling [12], in cancer modelling [10,21,30,40], and more specifically tumour growth [24,29], tumour immunology [41], brain cancer [42] or angiogenesis [16].…”
Section: Introductionmentioning
confidence: 99%